Pelatihan Doa Berbasis Modeling dan Penguatan Efektivitas Implementasi Teori Bandura Terhadap Self-Efficacy Religius Anak SD - Ni Putu Setya Dewi; Ni Nyoman Sudiani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This community service aims to examine the effectiveness of prayer training based on modeling and reinforcement in improving religious self-efficacy of grade 3 elementary school students at Pasraman Tirtha Bhuana Bekasi. The main problem faced is the low ability of students to memorize and recite daily prayers correctly and confidently. The method used is training based on Bandura's social learning theory through a pre-experimental one-group pretest-posttest design. The training was carried out in four sessions with stages of modeling, independent and group practice, positive reinforcement, and reflection. The pretest results showed that all students were not yet able to recite prayers correctly. After the training, there was a significant increase in students' ability and confidence in reciting prayers, as measured by posttest scores and normalized gain analysis. The conclusion shows that prayer training based on modeling and reinforcement is effective in building religious self-efficacy of elementary school students. Key words: Prayer Training, Modeling, Religious Self-Efficacy